Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 161626 by ZiYangLee last updated on 20/Dec/21

Commented by TheSupreme last updated on 20/Dec/21

f(x,y,λ)=x−2y+λ(4x^2 +9y^2 −16x−54y+61)   { ((1+λ(8x−16)=0)),((−2+λ(18y−54)=0)),((4x^2 +9y^2 −16x−54y+61=0)) :}  x=2−(1/(8λ))  y=3+(1/(9λ))  (4−(1/λ))^2 +(9+(1/λ))^2 −(32−(2/λ))−(162+(6/λ))+61=0    −35+(2/λ^2 )+(2/λ)=0  λ=(1/(−2±(√(144))))=(1/(2±12))=(1/(14)),−(1/(10))  x−2y=−4−(2/(9λ))−(1/(8λ))=−4−((25)/(72λ))  max = −4+((25)/(72))14=((−288+350)/(72))=1

f(x,y,λ)=x2y+λ(4x2+9y216x54y+61){1+λ(8x16)=02+λ(18y54)=04x2+9y216x54y+61=0x=218λy=3+19λ(41λ)2+(9+1λ)2(322λ)(162+6λ)+61=035+2λ2+2λ=0λ=12±144=12±12=114,110x2y=429λ18λ=42572λmax=4+257214=288+35072=1

Answered by mr W last updated on 20/Dec/21

say x−2y=k  ⇒x=k+2y  4(k+2y)^2 +9y^2 −16(k+2y)−54y+61=0  25y^2 −2(43−8k)y+4k^2 −16k+61=0  Δ=(43−8k)^2 −25(4k^2 −16k+61)≥0  k^2 +8k−9≤0  (k+9)(k−1)≤0  −9≤k≤1  ⇒(x−2y)_(min) =k_(min) =−9  ⇒(x−2y)_(max) =k_(max) =1

sayx2y=kx=k+2y4(k+2y)2+9y216(k+2y)54y+61=025y22(438k)y+4k216k+61=0Δ=(438k)225(4k216k+61)0k2+8k90(k+9)(k1)09k1(x2y)min=kmin=9(x2y)max=kmax=1

Commented by mr W last updated on 20/Dec/21

x−2y=−9 and x−2y=1 are two  lines which tangent the ellipse.

x2y=9andx2y=1aretwolineswhichtangenttheellipse.

Commented by mr W last updated on 20/Dec/21

Commented by ZiYangLee last updated on 20/Dec/21

Thank you !

Thankyou!

Answered by aleks041103 last updated on 20/Dec/21

4x^2 +9y^2 −16x−54y+61=  =(2x)^2 −2(2x)(4)+4^2 +(3y)^2 −2(3y)(9)+9^2 +61−4^2 −9^2 =  =(2x−4)^2 +(3y−9)^2 +61−16−81=0  ⇒(2x−4)^2 +(3y−9)^2 =6^2   ⇒(((x−2)/3))^2 +(((y−3)/2))^2 =1  ⇒((x−2)/3)=cos t       ((y−3)/2)=sin t  ⇒x=2+3cos t       y=3+2sin t  ⇒x−2y=3cost−4sint−4=  =5((3/5)cos t − (4/5)sin t)−4=  =5(cos θ cos t − sin θ sin t)−4=  =5cos(θ+t)−4  ⇒max(x−2y)=5max(cos(θ+t))−4=  =5−4=1

4x2+9y216x54y+61==(2x)22(2x)(4)+42+(3y)22(3y)(9)+92+614292==(2x4)2+(3y9)2+611681=0(2x4)2+(3y9)2=62(x23)2+(y32)2=1x23=costy32=sintx=2+3costy=3+2sintx2y=3cost4sint4==5(35cost45sint)4==5(cosθcostsinθsint)4==5cos(θ+t)4max(x2y)=5max(cos(θ+t))4==54=1

Commented by peter frank last updated on 20/Dec/21

thank you

thankyou

Answered by mr W last updated on 20/Dec/21

AN OTHER METHOD  4(x^2 −4x+4)+9(y^2 −6y+9)=36  (((x−2)^2 )/3^2 )+(((y−3)^2 )/2^2 )=1  center of ellipse is (2,3)  semi axises: a=3, b=2  say x−2y=k  line x−2y−k=0 should tangent the  ellipse.  3^2 ×1^2 +2^2 ×(−2)^2 =(2×1−2×3−k)^2   25=(4+k)^2   k+4=±5  ⇒k=−4±5=−9 or 1

ANOTHERMETHOD4(x24x+4)+9(y26y+9)=36(x2)232+(y3)222=1centerofellipseis(2,3)semiaxises:a=3,b=2sayx2y=klinex2yk=0shouldtangenttheellipse.32×12+22×(2)2=(2×12×3k)225=(4+k)2k+4=±5k=4±5=9or1

Commented by peter frank last updated on 20/Dec/21

thank you

thankyou

Terms of Service

Privacy Policy

Contact: info@tinkutara.com